Measurement of [Ypsilon] production in pp collisions at √s=13 TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Journal of high energy physics, 2018)
The production cross-sections of ϒ(1S), ϒ(2S) and ϒ(3S) mesons in proton-proton collisions at s√=13s=13 \sqrt{s}=13 TeV are measured with a data sample corresponding to an integrated luminosity of 277 ± 11 pb−1 recorded by the LHCb experiment in 2015. The ϒ mesons are reconstructed in the decay mode ϒ → μ+μ−. The differential production cross-sections times the dimuon branching fractions are measured as a function of the ϒ transverse momentum, pT, and rapidity, y, over the range 0 < pT < 30 GeV/c and 2.0 < y < 4.5. The ratios of the cross-sections with respect to the LHCb measurement at s√=8s=8 \sqrt{s}=8 TeV are also determined. The measurements are compared with theoretical predictions based on NRQCD. Open image in new window
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, F. Dordei, M. Dziewiecki, S. Esen, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 15.05.2019